When multinationals leave: A CGE analysis of the impact of divestments - Antonio G. Gómez Plana; María C. Latorre (Kiel Institute for the World Economy (IfW), 2013)
Most studies on Multinational Enterprises (MNEs) focus on the impact of their expansion through inward or outward foreign direct investment (FDI) flows. However, divestments are quite common among the operations of MNEs. In order to derive their effects, we have built a computable general equilibrium (CGE) model that includes two non-standard characteristics: the presence of MNEs, further extended to include unemployment. The model is applied to the Spanish economy, where FDI inflows have surpassed divestments at the aggregate level in the period 2005-2009. However, in ten sectors divestments are sizeable. Therefore, we analyse two different scenarios: 1) Divestments that imply the closure of plants of foreign affiliates; and 2) Divestments in which national firms buy the plant of the foreign affiliate. The model allows estimating the overall impact of the divestments occurring simultaneously in the ten sectors. We further, analyse the contrasting impact of divestments depending on the particular sector in which they take place. Results not only show that national acquisitions are less harmful than closures, but quantify those effects, and provide information on the divested-sector role. In any case, some adjustment costs arise in all scenarios.
Keywords: F23; F21; C68; 330; FDI; disinvestments; closures; national acquisitions; Spain